2003
DOI: 10.1038/sj.leu.2403034
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome after acute promyelocytic leukemia: the European APL group experience

Abstract: With improved treatment of acute promyelocytic leukemia (APL) by all trans retinoic acid (ATRA) combined to anthracycline-aracytin chemotherapy (CT), a larger number of those patients may be at risk of late complications. Recently, the Rome group reported five cases of myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML, non-APL) occurring during the course of 77 APL patients (6.5%) in complete remission (CR). From 1991 to 1998, we treated 677 newly diagnosed cases of APL, and 617 of them achieved CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
2
49
3
Order By: Relevance
“…In the reports of working groups with more intensive chemotherapy, for example, in the GIMEMA group using VP-16, the incidence of MDS or AML after APL treatment was 6.5%, whereas in the studies of European APL group which omitted the application of VP16 that incidence was 0.97%. 99,100 The cheaper prices of ATRA and ATO (provided by the Chinese pharmaceutical manufacturers) make them widely used in China. In some other developing countries like India and Iran ATO is also available, however, these two drugs are more expensive on international markets, especially ATO.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the reports of working groups with more intensive chemotherapy, for example, in the GIMEMA group using VP-16, the incidence of MDS or AML after APL treatment was 6.5%, whereas in the studies of European APL group which omitted the application of VP16 that incidence was 0.97%. 99,100 The cheaper prices of ATRA and ATO (provided by the Chinese pharmaceutical manufacturers) make them widely used in China. In some other developing countries like India and Iran ATO is also available, however, these two drugs are more expensive on international markets, especially ATO.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In APL patients, t-MDS and t-AML are sporadically reported [1,2], which were observed in about 6.5 % patients [3]. Patients usually developed t-MDS or t-AML with a latency ranging from 22 to 46 months after receiving chemotherapy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, therapy related MDS (t-MDS) is a long-term complication in APL. Separate studies by Lobe et al and Singh et al [10,11] reported average latency period of 46.5 and 62 months from onset of therapy for the primary hematological malignancy to the development of t-MDS respectively. Our patient manifested with severe marrow hypoplasia only 7 months after the diagnosis and initiation of APL treatment arguing against a possible diagnosis of t-MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of other clonal disorders such as PNH, MDS and AML in AA patients treated with immunosuppressive therapy has since been well recognized [3,4,6]. Similarly secondary MDS or AML developing following treatment of APL is also documented in the literature [10,14]. A primary insult to the bone marrow could simultaneously lead to several abnormal hematopoietic cell clones, with one dominating and others present below the threshold of detection.…”
Section: Discussionmentioning
confidence: 99%